Antagonistic, Cosmopolitan and Agonistic Memory Modes in Postmemorial Third-Generation Holocaust Narratives of Lithuanian Diaspora Writers - Greta Štikelytė (Politeja, 2023)
This article examines the challenges of coming to terms with Holocaust perpetratorship as depicted in postmemorial third-generation Holocaust literature by Lithuanian diaspora writers Rita Gabis, Julija Šukys, and Silvia Foti. It also outlines the mnemonic strategies used to reconcile contradictory historical narratives from the perspectives of both the victims and the perpetrators. The analysis demonstrates the authors’ approaches to portraying victims and perpetrators, their choices in framing conflicting historical accounts, and their exploration of individual actions within the context of collective national identities. The main variations observed in the structuring of conflict stem from differences in writing styles, levels of personal connection to familial history, and collective experiences of suffering. These variations are also intertwined with the deliberate silence surrounding the individual-historical narrative which the collective voluntarily retreated into.